Physio-Biochemical and Molecular Responses in Transgenic Cotton under Drought Stress - Muhammad Bilal Sarwar; Sajjad Sadıque; Sameera Hassan; Sania Rıaz; Bushra Rashıd; Bahaeldeen Babiker Mohamed; Tayyab Husnaın (Journal of Agricultural Sciences)
Drought decreases the growth and productivity in cotton. Heat shock proteins accumulate in plants under water stress to protect the biochemical and physiological processes at the molecular level. In this study, plants of T2 segregatinggenerationof transgenic cotton, containing small heat shock protein gene GHSP26 was compared with wild type plants for biochemical, physiological and molecular responses under different periods of drought stress. Transgenic plants accumulated 30% higher proline content than the wild type. Lipid peroxidation activity was reduced in transgenic plants which showed that the drought tolerance efficiency has been improved. Leaf relative water content was 69% and 45% in transgenic and wild-type plants, respectively at 10-day drought stress. Similarly, transgenic plants showed better performance for photosynthesis, stomatal conductance, transpiration and osmotic potential as compared to wild type. Real-time quantitative PCR of GHSP26 and some other drought responsive genes such as Gh-POD, Gh-RuBisCO, Gh-LHCP PSII, Gh-PIP, Gh-TPS and Gh-LEA have supported the higher expression and proved drought tolerance in transgenic plants. The overexpression of GHSP26 in transgenic plants improved the biochemical such as proline content and lipid peroxidation activity and physiological parameters like photosynthesis, osmotic potential and water related attributes. Hence, this study may be extended for selection of homozygous lines and breeding to improve the drought tolerance activity in plants